Relationship between physical fitness and game-related statistics in elite professional basketball players: Regular season vs. playoffs - Gomes,João Henrique (2017)
Abstract AIMS This study aimed to verify th erelation ship between of anthropometric and physical performance variables with game-related statistics in professional elite basketball players during a competition. METHODS Eleven male basketball players were evaluated during 10 weeks in two distinct moments (regular season and playoffs). Overall, 11 variables of physical fitness and 13 variables of game-related statistics were analysed. RESULTS The following significant Pearson’scorrelations were found in regular season: percentage of fat mass with assists (r = -0.62) and steals (r = -0.63); height (r = 0.68), lean mass (r = 0.64), and maximum strength (r = 0.67) with blocks; squat jump with steals (r = 0.63); and time in the T-test with success ful two-point field-goals (r = -0.65), success ful free-throws (r = -0.61), and steals (r = -0.62). However, in playoffs, only stature and lean mass maintained these correlations (p ≤ 0.05). CONCLUSIONS The anthropometric and physical characteristics of the players showed few correlations with the game-related statistics in regular season, and these correlations are even lower in the playoff games of a professional elite Champion ship, wherefore, not being good predictors of technical performance.